Heating external surfaces with heat pumps - Nowak , Krzysztof; Proszak-Miąsik, Danuta (Instal, 2020)
In unfavourable winter conditions we are forced to eliminate or mitigate the defects associated with the accumulation of snow and ice on pavements, stairs, driveways, parking lots, roofs, squares or sports fields. There are many ways to remove snow and ice from the surfaces under consideration, including chemical, mechanical or heating installations. Mechanical or manual methods do not always allow complete removal of snow and ice, while chemicals often have a negative impact on the environment. Electric or water heating is the most effective way of doing this. The paper presents the results of technical analysis of a parking lot heating system for cars with the use of a heat pump with a ground heat exchanger, as well as financial analysis of its application in the established conditions. From the cognitive point of view, it was interesting to examine whether the proposed installation is technically and economically feasible.